Consciousness Stage Implementation of Mosquito Nest Eradication (MNE) of Dengue Hemorrhagic Fever (DHF) - Ramadhani, Firdausi; Yudhastuti, Ririh; Widati, Sri (Humanistic Network for Science and Technology (Address: Cemara street 25, Ds/Kec Sukorejo, Ponorogo, East Java, Indonesia 63453), 2017)
The main obstacle to efforts to reduce the incidence of dengue fever due to the still not optimal program of Mosquito Nest Eradication (MNE). MNE is unlikely to be completed if community members reached the smallest neighborhood, ie households did not do it. The success of the termination of the chain of transmission of DHF was closely related to the awareness and responsibility of the community to want to maintain the cleanliness of the house and its environment. The main purpose of this research was to describe the public awareness of MNE DHF. This research used quantitative description approach. In this study as respondents were 332 people who were in Kamal Village, Kamal District. From the results of the study, it was found that most Kamal villagers were at the stage of Naival Consciousness. It was hoped that the community is in the critical consciousness stage to understand their environment. So it needed health education through Health Literacy to increase knowledge which then would generate critical consciousness so that society could do empowerment.